Patient and provider attitudes to emergency department-based HIV counselling and testing in South Africa - Bhakti Hansoti; Sarah E. Hill; Madeleine Whalen; David Stead; Andy Parrish; Richard Rothman; Yu-Hsiang Hsieh; Thomas C. Quinn (AOSIS, 2017)
Background: The national South African HIV Counselling and Testing (HCT) guidelines mandate that voluntary counselling and testing (VCT) should be offered in all healthcare facilities. Emergency departments (EDs) are at the forefront of many healthcare facilities, yet VCT is not routinely implemented in this setting. Methods: We conducted a cross-sectional study that surveyed patients and healthcare providers at a tertiary care ED in the spring and summer of 2016 to ascertain their attitudes to VCT in the ED. We also used two previously validated survey instruments to gather data on patients' HIV knowledge and providers' stigma against patients living with HIV, as we anticipated that these may have an impact on providers' and patients' attitudes to the provision of HIV testing within the ED, and may offer insights for future intervention development. Results: A total of 104 patients and 26 providers were enrolled in the study. Overall, patients responded more favourably to ED-based HIV testing (92.3%) compared to providers (only 40% responded favourably). When asked about potential barriers to receiving or providing HIV testing, 16.4% of patients and 24% of providers felt that the subject of HIV was too sensitive and 58.7% of patients and 80% of providers indicated that privacy and confidentiality issues would pose major barriers to implementing ED-based HIV testing. Conclusion: This study shows that while ED-based HIV testing is overall highly acceptable to patients, providers seem less willing to provide this service. The survey data also suggest that future development of ED-based testing strategies should take into consideration privacy and confidentiality concerns that may arise within a busy emergency care setting. Furthermore, every effort should be made to tackle HIV stigma among providers to improve overall attitudes towards HIV-positive individuals that present for care in the ED.